Effect of agarose bioplastic film enriched with Pleurotus sajor-cajor crude extract on wound healing in chicken embryo fibroblast - Kaewsiri, Natnaree; Rattanachan, Sitthichon; Punyadarsaniya, Darsaniya (Journal of Mahanakorn Veterinary Medicine, 2023)
The present study aims to verify the chemical characteristic of β-glucan in Pleurotus sajor-caju crude extract and its effect as enriched agarose bioplastic film on wound healing of scratched chicken embryo fibroblast (CEF) cells. Performed cell scratching assay on confluent monolayer CEF then assigned to 3 different treatment conditions, including blank agarose bioplastic film (agarose bioplastic film control), agarose bioplastic film enriched with 10-40 µg/ml of yeast β-glucan, and agarose bioplastic film enriched with 10-40 µg/ml of P. sajor-caju crude extract. This experiment was triplicated to observe wound healing at 0, 24, and 48 hours. The result shows the peak effect on wound healing in experimental groups, including yeast β-glucan 10 μg/ml, yeast β-glucan 20 μg/ml, and crude extract 40 μg/ml. In addition, the morphology of CEF cells post-treated by enriched agarose film appeared stellate-shaped with oval concentric nuclei. This finding might suggest the benefits of agarose bioplastic film-enriched Pleurotus sajor-caju crude extract on effective wound healing.